Miscue analysis: A glimpse into the reading process - Che Ton binti Mahmud; Revathi Gopal (Universitas Syiah Kuala, 2018)
This paper aims to analyse Form One students’ ability in reading prose. A qualitative research method was carried out involving 6 average ability students. The prose “Fair’s Fair” byNarinder Dhami was used as an instrument to gauge students’ ability in oral reading. The assessment carried out on the reading is miscue analysis, a tool to measure oral reading accuracy at the word level by identifying when and the ways in which the students deviates from the text while reading aloud. Miscues analysed are insertions, hesitation, omission, repetition and substitution. Miscues that maintain the meaning of the sentences are the participants’ strengths while miscues which disrupt the meaning of the sentences are the participants’ weaknesses. The data collected are analysed using descriptive statistics. The findings show that the percentage of strengths outweighed the percentage of weaknesses for all the participants on the occurrences of miscues. The students’ reading behaviour has provided insights into their language cueing system and the strategies they use during the reading process to comprehend a text.